Measurement of Bose-Einstein correlations in pp collisions at the LHC with CMS - Padula, Sandra S. [UNESP] (Iop Publishing Ltd, 2011)
Bose-Einstein correlations are measured in samples of charged particles produced in proton-proton collisions at 0.9 and 7 TeV center-of-mass energies, recorded by the CMS experiment at the LHC. The signal is observed in the form of an enhancement of number of pairs of the same-sign charged particles with small relative momentum. The dependence of this enhancement on kinematic and topological features of the event is studied.